Widening the Scope of Environmental Policies in North America Towards Blue Approaches (Governance, Development, and Social Inclusion in Latin America, 2018)
This edited volume provides a variety of insights into the context in which ocean and wetlands policy is placed at the sub-continental level. The governments of Mexico, Canada, and the United States of America have recognized the importance of conserving, protecting, and enhancing the environment in their territories. As a result, they have developed an institutional structure aimed at furthering environmental cooperation. However, marine environment has played a secondary role, characterized by scientific cooperation that does not develop into regional policies. This project analyzes how ocean and wetlands preservation is omitted from the North American Agreement on Environmental Cooperation, meaning that collaborative efforts under-perform or remain largely sidelined from mainstream issues. As contributors come from a mix of the social and natural sciences (politics, international relations, law studies, sociology, oceanology, and oceanography), this book presents diverse viewpoints on how to address wetlands protection, deep ocean research collaboration, and the marine context of the Sustainable Development Goals.